The role of in vitro cultivation on symbiotic trait and function variation in a single species of arbuscular mycorrhizal fungus. Issue 10 (October 2019) - Kokkoris, Vasilis; Hart, Miranda M.
Abstract: In vitro propagation of AM fungi using transformed root cultures (TRC) is commonly used to obtain pure AM fungal propagules for use in research and industry. Early observations indicate that such an artificial environment can alter traits and function of AM fungi over time. We hypothesized that increased in vitr o cultivation may promote ruderal strategies in fungi by enhancing propagule production and reducing mutualistic quality. To examine the effect of in vitro cultivation on the trait and function of AM fungi, we inoculated plants with 11 Rhizoglomus irregulare isolates which fell along a cultivation gradient spanning 80 generations. We harvested plants at 10, 20 and 30 d post inoculation to observe differences in fungal and plant traits post infection. In vitro cultivation led to increased spore production but reduced plant shoot phosphorus. Our results indicate that in vitro propagation may indirectly select for traits that affect symbiotic quality. Graphical abstract: Image 1 Highlights: There is widescale production of in vitro AM fungal propagules for use in agriculture, research and restoration. In vitro cultivation of AM fungi imposes selective pressure due to artificial growing conditions. Extensive in vitro cultivation leads to increased spore production but reduced phosphorus benefits to hosts. Thus in vitro propagation may indirectly select for traits that affect symbiotic quality.